Pertimbangan Turki Dalam Menyetujui EU-Turkey Statement 2016: Penanggulangan Pengungsi dan Irregular Migrants di Eropa - Omnif, Fitria Wulandari; Yusra, Muhammad; Jamilah, Maryam (Palito, 2023)
In 2016, European Union and Turkey had EU-Turkey Statement partnership to manage refugees flow who involved in irregular migration to EU. This partnership required Turki to reduce the irregular migration rate and to bring those irregular migrants back to Turkey. Turkey agreed on this agreement despite hosting a huge amount of refugees and being host country with the largest number of refugees globally. This study aimed to analyze the consideration done by Turkey in agreeing the partnership. The research method used is qualitative with descriptive approach. This study was analyzed with national security policy conceptual framework which explains state behavior in policy-making by Paul R. Viotti and Mark V. Kauppi. There are four considerations in policy making process such as interests and objectives, opportunities, threats, and capabilities. Based on the concept used, this study found that Turkey considered three things in agreeing EU-Turkey Statement 2016. Firstly, the interests and objectives from political and economical aspect which are EU membership negotiation, visa liberalization, and EU financial aid for taking care of refugees in Turkey. Secondly, the opportunities for Turkey to leverage/uplift its bargaining power. Thirdly, consideration about its capabilities in facing refugee flow in political, social, and economical aspects.